Alibaba’s growth frenzy : expanding by acquiring - Hou, Shiyu; Wei, W. (Bill); Yue, Tao (London : Rotterdam School of Management, Erasmus University, 2024)
While Alibaba’s growth from an apartment-sized company in 1999 to a company with the largest IPO value in American history in 2014 can only be high-velocity, founder Jack Ma’s taste for speed is relentless. Since early 2012 Alibaba Group has shifted gears and moved from organic growth and partnerships to high-speed growth by M&As in complementary technology fields. It has been expanding in finance, healthcare, travel and even movie making. Is it necessary for Alibaba to expand so aggressively? Is this seemingly "reckless" expansion really a lack of focus? What growth strategies work well for companies in emerging economies? How to compare the relative advantages of the different growth models – organic, collaboration and M&A? How does the business environment influence possible growth strategies – growing by diversification or focus on the core business? What are the key challenges for such high-speed growth? How do M&As lead to value creation for Alibaba?
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business -- Technological innovations -- China -- Case studies; Venture capital -- China -- Case studies; Consolidation and merger of corporations -- China -- Case studies